2021
DOI: 10.1016/j.gendis.2019.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic and antibacterial dual functions of a novel levofloxacin loaded mesoporous silica microspheres/nano-hydroxyapatite/polyurethane composite scaffold

Abstract: Lev/MSNs/n-HA/PU has been proved to be a novel scaffold material to treat bone defect caused by chronic osteomyelitis. We have previously identified that this material can effectively treat chronic osteomyelitis caused by Staphylococcus aureus in vivo . However, the potential mechanisms of antibacterial and osteogenic induction properties remain unclear. Thus, for osteogenesis property, immunohistochemistry, PCR, and Western blot were performed to detect the expression of os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Interested researchers have developed several methods to enhance the stability; bio-distribution, solubility, and selectivity of the IB drug in addition to the role of such techniques in controlling the released dosages of the drug, improving the patient compliance, and inducing its therapeutic efficiency. Introducing the drug at gradual delivery, managed dose, aggressively pursued, and targeted delivery using innovative carriers were recommended as promising methods to avoid all of the reported side effects. ,, The studied carriers for the IB drug involved mesoporous silica, hydroxyapatite, montmorillonite, titanium alloy, and MOFs. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Interested researchers have developed several methods to enhance the stability; bio-distribution, solubility, and selectivity of the IB drug in addition to the role of such techniques in controlling the released dosages of the drug, improving the patient compliance, and inducing its therapeutic efficiency. Introducing the drug at gradual delivery, managed dose, aggressively pursued, and targeted delivery using innovative carriers were recommended as promising methods to avoid all of the reported side effects. ,, The studied carriers for the IB drug involved mesoporous silica, hydroxyapatite, montmorillonite, titanium alloy, and MOFs. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Kuang et al 183 reported a dual-function PU scaffold with nano-hydroxyapatite (n-HAp) and mesoporous silica nanoparticles (MSNs). The resultant composite was loaded with levofloxacin and used to treat osteomyelitis and bacterial infections.…”
Section: Drugs-loaded Polyurethane Compositesmentioning
confidence: 99%
“… Drugs loaded in scaffolds Antibacterial mechanisms Bacterial species Ref. Tetracyclines PCL/MBG Doxycycline Inhibiting synthesis of protein S. aureus , E. coil, S. epidermidis, P. aeruginosa , [ 32 , 39 ] Gelatin/HA Tetracycline S. aureus [ 40 ] β-lactams CS/calcium phosphate cements; Penicillin Inhibiting synthesis of cell walls S. aureus [ 41 ] Agarose/nano hydroxycarbonateapatite Cephalexin [ 42 ] Aminoglycosides TiO 2 scaffold; Poly (glycidyl methacrylate)/hydroxyapatite Gentamicin Inhibiting synthesis of protein S. aureus , S. epidermidis, E. coli [ 25 , 43 , 44 ] Quinolones Polyurethane/silica/nano-hydroxyapatite Levofloxacin Inhibiting synthesis or function of nucleic acid S. aureus , E. coli [ 45 ] Monticellite Ciprofloxacin [ 46 ] Glycopeptides Baghdadite (Ca 3 ZrSi 2 O 9 ) Vancomycin Inhibiting synthesis of cell wall S. aureus [ ...…”
Section: Bioceramic-based Scaffolds With Drug-induced Antibacterial F...mentioning
confidence: 99%
“…Quinolones drugs represented by levofloxacin and ciprofloxacin are also widely used in the treatment of bone implant-associated infection due to their ability to penetrate into trabecular and cortical bone and thus minimize the risk of resistance selection [ 45 , 46 ]. For example, a novel polyurethane/mesoporous silica/nano-hydroxyapatite scaffold containing levofloxacin was developed by a foaming method [ 45 ]. The sustained release behavior of levofloxacin was significantly increased by encapsulating it in mesoporous silica nanoparticles.…”
Section: Bioceramic-based Scaffolds With Drug-induced Antibacterial F...mentioning
confidence: 99%